Differentiation of mass-serotype in infectious bronchitis virus local isolates using RT-PCR - A. Talip, Balkis; Omar, Abdul Rahman; Adzhar, Azri; Syed Hassan, Sharifah; Yap, May Ling; Arshad, Siti Suri (Universiti Putra Malaysia Press, 2004)
Avian infectious bronchitis is a highly contagious viral disease of chicken. Despite vaccination program the disease continues to occur in many countries partly because IBV can exist in many serotypes. Where good protection is obtained using homologous strain, heterologous strain may not provide any protection. Thus the isolation and identification of IB virus serotype is crucial in order to control the disease. Derivatives of Mass serotype vaccines have been used for a long time to control IBV. In many instances, Mass-serotype IBV is occasionally isolated in sporadic cases of IB disease. Whether the Mass serotype is the problem in that particular geographical area or the reversion of the Mass-serotype vaccine strain is not known. The objective of the study was to screen IBV local isolates for Mass serotypes using RT-PCR so that further study could be focus onto the non Mass-serotype. Out of 30 IBV local isolates, 7 isolates were found to be Mass-serotype and the remained are non-Mass serotype.